Focus Group Discussions-Agrobiodiversity Assessment - International Institute of Tropical Agriculture; International Food Policy Research Institute (International Food Policy Research Institute, 2017)
The project aimed at testing the hypothesis that the application of sustainable intensification technologies (cereal-legume-vegetable-livestock integrated systems) by smallholder households in North Ghana changes the level of inter and intra-specific crop diversity managed on-farm at household level. The project included two main activities: (1) analyses of the baseline socioeconomic survey data gathered by IFPRI and IITA from a diversity perspective; and (2) implementation and analysis of a series of focus group discussions in 12 communities to assess the overall diversity of plant species that households manage and derive benefits from. Study title: Focus Group Discussions-Agrobiodiversity Assessment Study description: A series of FGDs in 12 communities were carried out during the earlier part of 2016. The objective of FGDs on agricultural biodiversity was to elicit the local knowledge about the agricultural and useful wild biodiversity present in the study areas in order to generate: (a) an ordered inventory (list) of all useful plants used by local communities for human food, animal feed, medicine, fuel, etc. and their local names; and (b) an inventory of species and other products bought and sold in markets that people attend. The aim was to have a subjective assessment of the overall diversity of species households manage and derive benefits from, how important each species is and how it contributes to the household?s food and income, as well as how it is used. Project website: http://africa-rising.net